2018
DOI: 10.1177/0748233718795926
|View full text |Cite
|
Sign up to set email alerts
|

Dose and time-dependent effects of sodium fluoride on sperm motility: An in vitro study

Abstract: The present study was undertaken to investigate the toxic effects of sodium fluoride (NaF) on sperm motility and abnormality. Treatment of epididymal sperm suspensions with different doses of NaF (0.1, 1, 10, and 100 mg/ml) significantly reduced sperm motility at 15-and 30-min time intervals. Further, incubation at the same concentrations of NaF for 5-, 10-, and 15-min time intervals decreased sperm motility in a dose-and timedependent manner. The present investigation revealed for the first time the adverse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…The present study for the first time revealed that the adverse effect of ground water F on spermatozoa is dependent on duration of exposure. There was a time-dependent decrease in motility and activities of antioxidant enzymes and increase in abnormality and lipid peroxidation of spermatozoa due to treatment of ground water F. These results were similar to our previous study where treatment of NaF caused time-dependent depletion of motility of spermatozoa in in vitro (Chaithra et al, 2018). The present investigation involved two different in vitro experiments where spermatozoa were treated with ground water F at 0, 15, and 30 min time intervals.…”
Section: Discussionsupporting
confidence: 91%
“…The present study for the first time revealed that the adverse effect of ground water F on spermatozoa is dependent on duration of exposure. There was a time-dependent decrease in motility and activities of antioxidant enzymes and increase in abnormality and lipid peroxidation of spermatozoa due to treatment of ground water F. These results were similar to our previous study where treatment of NaF caused time-dependent depletion of motility of spermatozoa in in vitro (Chaithra et al, 2018). The present investigation involved two different in vitro experiments where spermatozoa were treated with ground water F at 0, 15, and 30 min time intervals.…”
Section: Discussionsupporting
confidence: 91%
“…Fluoride is a common chemical element with an effect on male fertility that has attracted much attention. 23 Fluoride-induced reductions in T levels and sperm motility have been detected in male rats, as described in a literature review. 24 Fluoride-induced OS has been reported to cause impaired antioxidant defense systems, mitochondrial dysfunction, and genotoxicity in animal models, and antioxidant intervention might be affected by antioxidants.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding the consumption of one serving of any of the brands analyzed by children over 9 years of age and the adult population, it does not pose a health risk, but it is necessary to consider that the percentage of contribution is significant (31.0%) and that other dietary sources of fluoride could increase the global intake with a consequent risk to health, leading to the appearance of dental or bone fluorosis, especially in young children, and neurological, heart and fertility problems, among others [ 24 , 41 , 42 ]. In all cases, moderate consumption should be recommended, since in consumption scenarios of two to three servings, the value of the ADI is already exceeded or close to 100%, depending on the age group.…”
Section: Resultsmentioning
confidence: 99%